Medication overuse reinstates conditioned pain modulation in women with migraine. (May 2018) - Guy, Nathalie; Voisin, Daniel; Mulliez, Aurélien; Clavelou, Pierre; Dallel, Radhouane
Background: This study investigated the effects of medication overuse and withdrawal on modulation of pain processing in women with migraine. Temporal summation of laser-evoked thermal pain was used to measure the effects of conditioned pain modulation. Methods: 36 female participants (12 healthy volunteers, 12 with episodic migraine and 12 with medication overuse headache) were included in a two session protocol. Medication overuse headache subjects were also tested three weeks after medication overuse headache withdrawal. Mechanical and laser-evoked thermal pain thresholds were measured on the back of the non-dominant hand where, later, temporal summation of laser-evoked thermal pain to repetitive thermal stimuli was elicited for 30 min, at an intensity producing moderate pain. Between the 10 th and 20 th minutes, the contralateral foot was immersed into a water bath at a not painful (30℃) or painfully cold (8℃; conditioned pain modulation) temperature. Results: Episodic migraine, medication overuse headache and medication overuse headache withdrawal were associated with an increase in extracephalic temporal summation of laser-evoked thermal pain as compared to healthy volunteer subjects, while there was no alteration of laser-evoked thermal and mechanical extracephalic pain thresholds in these subjects. Conditioned pain modulation was highly efficient in temporal summation of laser-evoked thermal pain in healthy volunteer subjects, with a solid post-effect (reduction of pain). Conditioned pain modulation was still present, but reduced, in episodic migraine. By contrast, conditioned pain modulation was normal in medication overuse headache and strongly reduced in medication overuse headache withdrawal. Furthermore, in medication overuse headache withdrawal, the post-effect was no longer a decrease, but a facilitation of pain. Conclusions: These data show that a decrease in conditioned pain modulation does not underlie medication overuse headache in women. On the contrary, medication overuse reinstated conditioned pain modulation in female migraine patients. They also identify different phenotypes of pain modulation in migraine patients. Registration number N° 2008-A00471-54.